(untitled) (Indian Journal of Animal Production and Management, 2025)
The pancreas is a vital organ with both endocrine and exocrine functions in mammalian species. This report presents a comparative study of the ultrastructural characteristics of pancreatic tissue in the rabbit (Oryctolagus cuniculus) and guinea pig (Cavia porcellus) using scanning electron microscopy (SEM). Pancreas specimens were obtained from healthy adult animals on the University of Muthanna and processed for SEM using standard techniques for SEM processing. This study has documented different sizes of acinar cells, ductal structure, and organization of islets between the two species. The rabbit pancreas exhibited larger acini than guinea pig pancreas with more larger zymogen granules than that in the guinea pig. In contrast, the guinea pig pancreas exhibited more acinar units more densely packed with smaller acinar and cellular dimensions. Additionally, the ductal system of the rabbit pancreas exhibited more branching than that of the guinea pig pancreas. The current study adds to our knowledge of comparative pancreatic morphology to different species, regardless of physiological functional similarities, which has intrinsic importance in future studies involving comparative physiology or as an experimental model.